Prehabilitation and Rehabilitation for Patients with Lung Cancer: A Review of Where we are Today. Issue 11 (November 2022) - Burnett, C.; Bestall, J.C.; Burke, S.; Morgan, E.; Murray, R.L.; Greenwood-Wilson, S.; Williams, G.F.; Franks, K.N.
Abstract: Lung cancer is the third most common type of cancer in the UK, with nearly 50 000 new cases diagnosed a year. Treatments for lung cancer have improved in recent years with the advent of new surgical and radiotherapy techniques and the increased use of immunotherapies. These advances have resulted in increasing numbers of patients surviving beyond the completion of their treatment. Lung cancer patients are now not dying from their cancer diagnosis, but from other co-existing pathologies. Lung cancer patients commonly present with multiple comorbidities. Mitigating the effects of poor lifestyles and changing behaviours may improve the efficacy of treatments, reduce side-effects and improve the quality of life for lung cancer patients. Published evidence supports the use of interventions to manage behavioural habits, to optimise the health of patients. There is no consensus as to what, when or how to embed these into the patient pathway. Supporting patients before, during and after their cancer treatments to increase activity, eat well and stop smoking have been seen to decrease side-effects and improve patient outcomes and wellbeing. The challenge is to provide a package of interventions that is acceptable to patients and fits within the patient pathway so as not to conflict with diagnostic and therapeutic activities. This article reviews where we are today with providing behavioural support to optimise the health of lung cancer patients undergoing treatment. Highlights: Patients are surviving their cancer treatments and are living with their comorbidities. Optimising the health of lung cancer patients will reduce treatment side effects and improve the quality of life. How and when should lifestyle interventions be offered to lung cancer patients?.